1995
DOI: 10.1006/viro.1995.1196
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies in Human Sera Specific to Hypervariable Region 1 of Hepatitis C Virus Can Block Viral Attachment

Abstract: It has been postulated that antibodies specific to the hypervariable region 1 (HVR1) within the putative envelop protein E2 of hepatitis C virus (HCV) can neutralize virus. We studied such antibodies in sera of patients who were infected in a single-source outbreak by a contaminated anti-D immunoglobulin preparation (HCV-AD78). The nucleotide sequences of cDNAs encoding HVR1 of HCV-AD78 were determined. The four major variants (HVR1.A, B, C, and D) were expressed as fusion proteins in Escherichia coli. Sixty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
168
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(171 citation statements)
references
References 0 publications
2
168
0
1
Order By: Relevance
“…However, it has also been shown that a humoral immune response against HCV envelope glycoproteins, in particular against the HVR1, correlated with the clearance of this virus (3,4). It is often not possible to obtain sufficiently early and frequent samples from humans to study the temporal course of viremia, cell-mediated immune responses, and antibody responses and, therefore, experimentally infected chimpanzees offer a significant advantage for studying HCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been shown that a humoral immune response against HCV envelope glycoproteins, in particular against the HVR1, correlated with the clearance of this virus (3,4). It is often not possible to obtain sufficiently early and frequent samples from humans to study the temporal course of viremia, cell-mediated immune responses, and antibody responses and, therefore, experimentally infected chimpanzees offer a significant advantage for studying HCV.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the humoral immune response is less well defined. Nevertheless, it has been shown that an antibody response against the envelope proteins, in particular the hypervariable region 1 (HVR1) of E2, correlated with viral clearance (3,4). In vitro and in vivo studies demonstrated that certain antibodies neutralized HCV and͞or blocked attachment of HCV to target cells and prevented infection (reviewed in ref.…”
mentioning
confidence: 99%
“…The quasispecies nature of HCV seemed to relate to the pathogenesis of persistent infection 8,9,22,23 and to the effectiveness of interferon therapy, 5,10,11 but its pathogenetic significance is still unknown. Although, hepatocytes are thought to be the principal site of HCV replication, there have only been a few studies on the quasispecies nature of liver [12][13][14]24 and the results of these studies were conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of experimental evidence argue in favor of a dominant role of positive selection for amino acid changes in driving the pattern of HVR1 genetic diversification (1,2). Prospective studies of serological responses to synthetic oligopeptides derived from HVR1 sequences of patients with acute and chronic HCV infection showed apparently extensive serological cross-reactivity for unrelated HVR1 peptides in the majority of the patients (3)(4)(5)(6)(7)(8)(9). A significant correlation was found between HVR1 sequence variation and the intensity and cross-reactivity of humoral immune responses, strongly supporting the contention that HCV variant selection is driven by the host immune response (9).…”
mentioning
confidence: 99%